Analisis Kemampuan Membaca Pemahaman Siswa Kelas III SDN 3 Ketapang Raya - Widya Apriani; Nurul Kemala Dewi; Siti Istiningsih (Journal of Classroom Action Research, 2022)
Reading is a receptive language skill. This study aimed to desctibe the reading comprehension skill experienced by third-grade students at SDN 3 Ketapang Raya. This study employed descriptive qualitative method and applied observation, documentation, interviews, and tests to collect the data. This study elaborated on data collection techniques from Milles and Hubberman to analyze the data. It included data collection, reduction data, data presentation, conclusions, and verification. The results indicated that several types of reading comprehension skills experience by students were: not understanding the text, low reading ability, difficulty in concentrating, careless toward punctuation marks, not being able to re-explain the text, and the last distress was recalling the text. Off all the reading skill types above, the most prominent experience was a lack of understanding of punctuation marks and difficulty to re-create the texts. The difference between this study and previous studies was that the previous one only wanted to know the students’ reading comprehension skills using story texts. In contrast, this study observed the students’ reading comprehension skills and investigated the types of students’ reading comprehension skills.